KECERNAAN BAHAN KERING DAN BAHAN ORGANIK PAKAN YANG MENDAPAT SUPLEMENTASI UREA MOLLASES MULTINUTRIENT BLOK (UMMB) DARI BEBERAPA JENIS LIMBAH PERTANIAN DAN RUMPUT LAPANG - Belo, Suprianto; Tuturoong, Ronny; Maaruf, Kartini (ZOOTEC, 2018)
DRIED MATERIALS AND ORGANIC MATERIALS WHICH ARE SUPPLYING UREA MOLLASES MULTINUTRIENT BLOCKS OF (UMMB) FROM SEVERAL AGRICULTURAL WASTE AND EQUIPMENT GRASS. The common forages are given for ruminants in the form of grasses coming from pastures or lawns, bunds, and roadside. In addition, there are still sources of animal feed that has not been utilized optimally the agricultural waste. Some obstacles to the utilization of agricultural waste as animal feed is caused by the generally low quality of agricultural waste with high fiber content, low protein, and low digestibility so that when it is used as a basal feed it is necessary to add other feed ingredien ts that have good quality to meet the needs livestock in improving productivity. One way to optimize the nutritional value of agricultural waste is by providing feed supplements such as urea molasses multinutrient block (UMMB). The research was conducted in Tonsewer Village, Tompaso Barat District for 40 days starting from November 2016 until December 2016. The animals used in this study were male PO cattle, aged 12 - 18 months as many as 4 tails with weight Â± 100 kg and feed given is field grass (RL), corn straw (JJ), rice straw (JP), and groundnut straw (JKT), and UMMB as a supplement feed. This study used a 4 x 4 Latin Square Design experiment with 4 cattle and 4 treatments. The results of this study indicate that the diversity analysis showed that the treatment had significantly different effect (P <0.05) on the consumption and digestibility of BK and BO. The digestibility of feedstuff DM was R1 (67,51%), R2 (68,57%), R3 (63,51%) and R4 (72,78%) and BO digestibility was R1 (72,78%) , R2 (74.22%), R3 (67.33%), and R4 (67.33%).Â Key words: crop residues, UMMB, DM, OM digestibility and ongole crossbred cattle